Management Of The Revitalization Of Vocational School (SMK) Revitalization As An Effort To Improve The Quality And Competitiveness Of Graduates (Study At SMKN 3 Pamekasan) - Winda Fashihah; Suryadi; Ainul Hayat (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The Vocational High School Revitalization Policy (SMK) is a Presidential Instruction (Inpres) Number 9 of 2016 concerning